1997
DOI: 10.1051/jp2:1997219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matrix Molecular Weight on a Brush - Like Surface Layer Formed by a Polymer Functionalised at Both Ends

Abstract: Deuteropolystyrene has been functionalised at each end by fluorosilane groups, the polymer obtained had a relative molar mass of 98 ×103. Thin films of this polymer mixed with unfunctionalised hydrogenous polystyrene have been prepared and the blends annealed to equilibrium at 413 K. The distribution of the end functionalised deuteropolymer was obtained by neutron reflectometry and a range of molecular weights of the hydrogenous polystyrene matrix has been used. In all cases the deutero polystyrene was prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Influence of the fluorocarbon group and film thickness Figure 5 also shows the distribution of NDPS, the deutero polymer without the fluorocarbon end group, and it appears that the group has only a modest influence on the distribution. This is surprising because previous reports [8,12,31,32] show it to cause surface adsorption significantly in excess of that of the unmodified polymer.…”
Section: Approach To Equilibriummentioning
confidence: 73%
See 2 more Smart Citations
“…Influence of the fluorocarbon group and film thickness Figure 5 also shows the distribution of NDPS, the deutero polymer without the fluorocarbon end group, and it appears that the group has only a modest influence on the distribution. This is surprising because previous reports [8,12,31,32] show it to cause surface adsorption significantly in excess of that of the unmodified polymer.…”
Section: Approach To Equilibriummentioning
confidence: 73%
“…Figures 8 and 9 show the volume fraction profiles obtained from the data fitting for bilayers with the lowest and highest molecular weight (H47 and H1700) hydrogenous polymers on top of the NDPSF m layer. For each composition profile the excess, z * , at each interface (where appropriate) was obtained using the relation (5) and the ellipsometric thickness [31] of each interfacial surface excess layer, L, from…”
Section: Neutron Reflectometry Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the main, polymer brushes are generally discussed when the molecules are attached to a planar surface and experimental studies in both bulk melts and dilute solutions have been reported. [37][38][39][40][41][42][43][44][45][46] Initially, the concept of stretching was confined to stars in dilute solution, but given the theoretical predictions, confirmed to some extent by experiment, of the stretched dry brush state, it is perhaps not surprising that we have observed stretching of the single labeled arm in the multiarm stars. Past experimental work has inferred the stretching of star arms from the global dimensions of the star polymers; 3,9,47 we have reported here a direct observation of this stretching for one arm of the star.…”
Section: Discussionmentioning
confidence: 96%
“…Beside the homogeneous layer model, Gaussian, exponential, and parabolic functions based on scaling theories have been used to analyze the reflectivity profiles. [25][26][27][28] Thermoresponsive polymer brushes are ideal samples for the proof-of-principle demonstration of our novel approach of modelling NR data. The fact that they can be stimulated into different hydration states while maintaining a fixed mass of polymer on the surface provides a self-consistent test of the method.…”
Section: Introductionmentioning
confidence: 99%